Black Carbon aerosol measurements and simulation in two cities in south-west Spain. (February 2016) - Milford, Celia; Fernández-Camacho, R.; Sánchez de la Campa, A.M.; Rodríguez, Sergio; Castell, Nuria; Marrero, Carlos; Bustos, J.J.; de la Rosa, J.D.; Stein, Ariel F.
Abstract: Black carbon (BC) has been simulated for south-west Spain with the air quality model CAMx driven by the MM5 meteorological model, with a spatial resolution of 2 km × 2 km and a temporal resolution of 1 h. The simulation results were evaluated against hourly equivalent black carbon (EBC) concentrations obtained in the cities of Seville and Huelva for a winter period (January 2013) and a summer period (June 2013). A large seasonal variability was observed in PM2.5 EBC concentration in the two cities, with higher concentrations in wintertime; summertime EBC concentrations were typically less than half those of the wintertime. The model captured the large diurnal, seasonal and day to day variability in these urban areas, mean biases ranged between −0.14 and 0.07 μg m −3 in winter and between 0.01 and 0.29 μg m −3 in summer while hourly PM2.5 EBC observations ranged between 0.03 μg m −3 to 10.9 μg m −3 . The diurnal variation in EBC concentrations was bimodal, with a morning and evening peak. However, the EBC evening peak was much smaller in summer than in winter. The modelling analysis demonstrates that the seasonal and day to day variability in EBC concentration in these urban areas is primarily driven by the variation in meteorological conditions. An evaluation of the role of regional versus local contributions to EBC concentrations indicates that in the medium size city of Seville, local on-road sources are dominant, whereas in the small size city of Huelva, local as well as regional sources produce a similar contribution. Considering the large diesel share of the vehicle fleet in Spain (currently ∼ 56%), we conclude that continued reduction of BC from diesel on-road sources in these urban areas is indeed a priority, and we suggest that targeted mitigation strategies, for example reducing the heaviest emitters in wintertime, would yield the greatest benefits. Highlights: Black Carbon is measured with high temporal resolution at two city sites. We evaluate CAMx Black Carbon simulations during a winter and summer period. Results show meteorology drives Black Carbon seasonal variability in these urban areas. Targeted mitigation strategies during wintertime are recommended.